2019
DOI: 10.1590/2179-8087.006019
|View full text |Cite
|
Sign up to set email alerts
|

Urochloa decumbens Has Higher Mycorrhizal Colonization in Degraded than in Pristine Areas in the Brazilian Cerrado

Abstract: Brazil has extensive degraded areas, where vegetation fails to establish due to harsh soil conditions. However, some invasive species such as Urochloa decumbens are successful pioneers in such areas, but the reasons deserve investigation. Mycorrhizal fungi are abundant in Cerrado soils, and their association with plants are beneficial for their establishment in natural and degraded areas. This study investigated whether arbuscular mycorrhizal colonization of native and exotic plants in the Cerrado differs betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Nonetheless, because U. decumbens is highly colonized by AM, it has been used in initial stages of land restoration programs in disturbed areas, where other species do not grow well under harsh soil conditions (Leite et al, 2019). Also, Urochloa is highly responsive to the increased availability of nutrients after fires (Pereira-Silva et al, 2019).…”
Section: Urochloa As An Invasive Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, because U. decumbens is highly colonized by AM, it has been used in initial stages of land restoration programs in disturbed areas, where other species do not grow well under harsh soil conditions (Leite et al, 2019). Also, Urochloa is highly responsive to the increased availability of nutrients after fires (Pereira-Silva et al, 2019).…”
Section: Urochloa As An Invasive Speciesmentioning
confidence: 99%
“…It has been found that in nutrient-poor pastures, Urochloa depends more on mycorrhizal fungi than C3 plants, especially in the initial seedling stages and during regrowth after periods of drought (Hetrick et al, 1990;Veenendaal et al, 1992). The use of U. decumbens in pastures in the Brazilian Cerrado has revealed high colonization by AMF, at a greater degree than native plants (Leite et al, 2019), which would partially explain the capacity of this species to develop in low fertility soils.…”
Section: P Cyclingmentioning
confidence: 99%
“…Urochloa eminii legacies and invaded inocula caused high levels of root mycorrhizal colonization for both species, in line with evidence that U. eminii is a very efficient AMF propagator, through effectively changing the soil microbiota; it is even used in laboratories for mycorrhizal spore propagation (Banuelos et al 2014). Recent evidence also suggests U. eminii has the ability to accumulate spores in Cerrado areas invaded with exotic grasses (Leite et al 2019). Therefore, any living soil in which U. eminii has grown should generate large amounts of mycorrhizal spores, ultimately affecting future colonizers of any soil patch.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of the Urochloa root system with the soil microbiota can also help form and stabilize soil aggregates and increase porosity. Urochloa is highly colonized by mycorrhizas, which, in part, explains their ability to grow in low-fertility soils (Smith and Read, 2010;Leite et al, 2019;Baptistella et al, 2020). This characteristic is exciting since coffee is also quite colonized and depends on mycorrhizas to acquire nutrients, mainly P, and contributes to the positive water status of coffee plants (Andrade et al, 2009(Andrade et al, , 2010.…”
Section: Urochloa Intercropping With Coffeementioning
confidence: 99%